EFFECT OF HORMONAL AND HERBAL THERAPIES ON PUERPERAL EVENTS AND POSTPARTUM PLASMA PROFILE OF GLUCOSE AND TOTAL PROTEIN IN HOLSTEIN FRIESIAN COWS - Patel, B B; Patel , D M; Patel , J A (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Twenty-eight recently calved HF cows of University farm were monitored through clinical diagnosis and fortnightly plasma profile of glucose and total protein from the day of calving till 75 day postpartum to study effect of hormonal and herbal therapies on postpartum events. The animals were equally divided into four groups, each of seven animals. Group I served as Control; Group II received herbal ecbolic (Vantab), 3 intra uterine infusions at weekly interval postpartum. Group III Oxytocin 50 units and PGF2α 25 mg (Iliren) i/ m immediately after parturition and Group IV only PGF2α 25 mg (Iliren) i/m immediately after parturition. The overall mean time for regression of pregnancy CL, Uterine involution, first estrous postpartum and service period was 8.50±0.81, 29.71±0.71, 31.65±1.45 and 122.39±6.90 days, respectively. The influence of therapy was significant on uterine involution and first estrous postpartum, being lowest in PG treated groups. The overall mean plasma glucose concentrations in cows was 57.79 ± 0.50 (range 50 to 67) mg %. The differences between treatment groups and between periods were highly significant (P<0.01). The fortnightly mean values of glucose from parturition (0 day) to 75 day postpartum were observed to be 63.25 ± 1.32, 52.25 ± 1.19, 52.46 ± 1.24, 55.57 ± 1.19, 59.03 ± 1.10 and 60.67± 1.19 mg/dl, respectively. The values for glucose increased 60 days postpartum. The overall plasma total protein concentration was 7.25 ± 0.05 (range 6.65 to 7.87) g/dl. There was no significant difference between groups, but the period effect was significant (P<0.05). The fortnightly values were 7.23 ± 0.07, 6.92 ± 0.16, 6.90 ± 0.14, 7.70 ± 0.15, 7.43 ± 0.17 and 7.52± 0.13 g/dl, from parturition (0 day) to 75 day postpartum, respectively.